Pharmacokinetic Characterization of ZT55, A Novel Indole Derivative Isolated from Radix Isatidis, using Liquid Chromatography/Tandem Mass and Q-TOF/Tandem Mass Spectrometry - Dan, Zhang; Min, Hu; Chengbo, Xu; Chengjuan, Chen; Jiangong, Shi; Tiantai, Zhang; Pengmei, Li (Current Pharmaceutical Analysis, 2021)
Background: ZT55 is a novel natural product isolated from Radix isatidis. It is a highlyselective tyrosine kinase inhibitor against myeloproliferative neoplasms. Although earlier research has described the pharmacodynamic properties of ZT55 in vivo and in vitro, the quantitative determination and pharmacokinetic profile in vivo have not been thoroughly studied. Methods: A novel liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed and validated for the quantification of ZT55 in rat plasma. A Waters symmetry C18 column was used for chromatographic separation; 0.1% formic acid in acetonitrile and 0.1% formic aqueous solution was used as the mobile phase. Detection was performed by Multiple Reaction Monitoring (MRM) mode using electrospray ionization in the positive ion mode. UPLC-QTOF-MS was used for the identification of metabolites. Results: The method was linear (R2=0.9988) over the concentration range of 1-2500 ng/mL. The lower limit of quantification was 1 ng/mL. The intra-day and inter-day precision of ZT55 showed a relative standard deviation within 8.47%, whereas the accuracy (RE) ranged from -4.84% to 4.45%. The recoveries ranged from 92.89% to 97.21%. ZT55 reached the highest plasma concentration at 0.5h. The peak concentrations with three dosages were 103.59±10.11, 185.23±29.56, and 355.98±28.86 ng/mL. The AUC0-24 of three dosages were 874.70±72.33, 433.80±49.33, and 231.65±19.41 ng•h/ml respectively. Five metabolites of ZT55 from plasma were confirmed. The main pathways of ZT55 in vivo were hydrolysis, N-dealkylation, glycosylation, and sulfonation. Conclusion: LC-MS/MS method was successfully applied to the pharmacokinetic study of ZT55 after oral administration and intravenous. ZT55 exhibited rapid oral absorption, high elimination, and low absolute bioavailability. This study provides important pharmacokinetic and metabolism information for further pharmacological and toxicological research on ZT55.
Keywords: ZT55